Strategic policies and growth: an applied model of R&D-driven endogenous growth - Diao, Xinshen; Roe, Terry L.; Yeldan, A. Erinc (Elsevier, 1999)
...Utilizing evidence from recent econometric studies on sources of growth, the model also accounts explicitly for cross-border technological spillovers. The model is specified and calibrated to data from Japan, and is solved to obtain both the transitional and the steady-state equilibria. We explore the effects of selective trade and R&D promotion policies on long-run growth and social welfare. The model results suggest that while a strategic trade policy has little effect on re-allocating resources into domestic R&D activities, it can significantly affect the cross-border spillovers of technological knowledge, which, in turn, stimulates growth. We find that trade liberalization may cause the growth rate to fall and lead to a loss of social welfare in the long-run, although it improves welfare in the short-run. R&D promotion policies stimulate growth by inducing private agents to allocate more resources to domestic R&D, as well as to take greater advantage of global R&D spillovers. Here, we find significantly high growth effects together with sizable gains in social welfare at low incidence to tax payers.